Ruch i choreoterapia jako konieczny element funkcjonowania w okresie późnej dorosłości - Kott, Michał (2017)
The purpose of the article is to show the importance of motion and physical activity in maintaining the condition of a person over 60 years old. The text outlines the state of research into the physical activity of late adulthood, focusing on the beneficial role of dance, which, besides sustaining physical fitness, allows the body to maintain control over the body and control emotion. Regardless of that, dance helps to improve intellectual and social abilities.
Keywords: physical activity; social contacts; choreotherapy; dance; motion; seniors